2022
DOI: 10.3390/antiox11091818
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Gastrointestinal Behavior of the Coffee Pulp Phenolic Compounds under Simulated Conditions

Abstract: Numerous residues, such as the coffee pulp, are generated throughout coffee processing. This by-product is a source of antioxidant phytochemicals, including phenolic compounds and caffeine. However, the antioxidant properties of the phenolic compounds from the coffee pulp are physiologically limited to their bioaccessibility, bioavailability, and biotransformation occurring during gastrointestinal digestion. Hence, this study explored the phenolic and caffeine profile in the coffee pulp flour (CPF) and extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 49 publications
(66 reference statements)
0
6
0
Order By: Relevance
“…Neochlorogenic, chlorogenic, cryptochlorogenic, and p-coumaroylquinic acids increased after the gastric phase. The increase in caffeoylquinic acid derivatives can be attributed to the decrease in di-caffeoylquinic acid compounds resulting from fragmentation and the subsequent formation of these compounds [ 40 ]. It has been reported that the stability of di-O-caffeoylquinic acids is low, and depending on pH and temperature conditions, diCQAs can isomerise with each other and transform into mono-CQAs, caffeic acid, and compounds with the formula C 15 H 14 O 6 [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Neochlorogenic, chlorogenic, cryptochlorogenic, and p-coumaroylquinic acids increased after the gastric phase. The increase in caffeoylquinic acid derivatives can be attributed to the decrease in di-caffeoylquinic acid compounds resulting from fragmentation and the subsequent formation of these compounds [ 40 ]. It has been reported that the stability of di-O-caffeoylquinic acids is low, and depending on pH and temperature conditions, diCQAs can isomerise with each other and transform into mono-CQAs, caffeic acid, and compounds with the formula C 15 H 14 O 6 [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…As expected in all samples, the amount of individual phenolics increased from the oral to the gastric phase. 73 Compared to the previous digestion step, after intestinal digestion (IN+OUT), the amount of neochlorogenic, chlorogenic, and caffeic acids decreased in all samples, while the amount of other determined compounds (gallic acid, ellagic acid, ferulic acid, and rutin) either decreased or increased depending on the samples. Cyn-3-O-glc and pn-3-O-glc were only detected in the gastric phase of fresh, VD, and FD samples; no anthocyanins were recovered after intestinal digestion.…”
Section: Resultsmentioning
confidence: 79%
“…The change of individual phenolics and anthocyanins (mg/100 g dw) upon digestion is given in Table . As expected in all samples, the amount of individual phenolics increased from the oral to the gastric phase . Compared to the previous digestion step, after intestinal digestion (IN+OUT), the amount of neochlorogenic, chlorogenic, and caffeic acids decreased in all samples, while the amount of other determined compounds (gallic acid, ellagic acid, ferulic acid, and rutin) either decreased or increased depending on the samples.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanisms of controlling blood sugar and lipids are likely through the inhibition of intestinal cholesterol absorption [ 8 ] and antioxidative effects from polyphenols such as chlorogenic acid (CGA), epicatechin (EC), and catechin [ 30 , 31 ]. Interestingly, a previous in vitro simulated gastrointestinal digestion study reported that the phenolic acids and caffeine in coffee pulp extract were more bioaccessible than flavonoids [ 33 ]. Thus, phenolic acids are likely to contribute to the antioxidant activities and the blood-lipid-lowering effect of coffee cherry pulp juice concentrate.…”
Section: Discussionmentioning
confidence: 99%